Techno-economic feasibility of selective CO2 capture processes from biogas streams using ionic liquids as physical absorbents - García-Gutiérrez, Pelayo; Jacquemin, Johan; McCrellis, Corina; Dimitriou, Ioanna; Taylor, S.F. Rebecca; Hardacre, Christopher; Allen, Raymond W.K. (American Chemical Society, 2016)
Biogas from anaerobic digestion of sewage sludge is a renewable resource with high energy content, which is composed mainly of CH4 (40-75 vol %) and CO2 (15-60 vol %). Other components, such as water (H2O, 5-10 vol %) and trace amounts of hydrogen sulfide and siloxanes, can also be present. A CH4-rich stream can be produced by removing the CO2 and other impurities so that the upgraded biomethane can be injected into the natural gas grid or used as a vehicle fuel. The main objective of this paper is to assess the technical and economic performance of biogas upgrading processes using ionic liquids that physically absorb CO2. The simulation methodology is based on the COSMO-SAC model as implemented in Aspen Plus. Three different ionic liquids, namely, 1-ethyl-3-methylimidazolium bis(trifluoromethyl)sulfonylimide, 1-hexyl-3-methylimidazoliumbis(trifluoromethyl)sulfonylimide, and trihexyl(tetradecyl)phosphonium bis(trifluoromethyl)sulfonylimide, are considered for CO2 capture in a pressure-swing regenerative absorption process. The simulation software Aspen Plus and Aspen Process Economic Analyzer is used to account for mass and energy balances as well as equipment cost. In all cases, the biogas upgrading plant consists of a multistage compressor for biogas compression, a packed absorption column for CO2 absorption, a flash evaporator for solvent regeneration, a centrifugal pump for solvent recirculation, a preabsorber solvent cooler, and a gas turbine for electricity recovery. The evaluated processes are compared in terms of energy efficiency, capital investment, and biomethane production costs. The overall plant efficiency ranges from 71 to 86%, and the biomethane production cost ranges from 9.18-11.32 per GJ (LHV). A sensitivity analysis is also performed to determine how several technical and economic parameters affect the biomethane production costs. The results of this study show that the simulation methodology developed can predict plant efficiencies and production costs of large scale CO2 capture processes using ionic liquids without having to rely on gas solubility experimental data.